Differences in Biogeographic Patterns and Mechanisms of Assembly in Estuarine Bacterial and Protist Communities - Weiyue Zhang; Yunlei Zhang; Zhizhuo Shao; Yi Sun; Hongjun Li (Microorganisms)
As transitional ecosystems between land and sea, estuaries are characterized by a unique environment that supports complex and diverse microbial communities. A comprehensive analysis of microbial diversity and ecological processes at different trophic levels is crucial for understanding the ecological functions of estuarine ecosystems. In this study, we systematically analyzed the diversity patterns, community assembly, and environmental adaptability of bacterial and protist communities using high-throughput sequencing techniques. The results revealed a higher alpha diversity for the bacteria than for protists, and the beta diversity pattern was dominated by species turnover in both communities. In addition, the two community assemblages were shown to be dominated by deterministic and stochastic processes, respectively. Furthermore, our results emphasized the influence of the local species pool on microbial communities and the fact that, at larger scales, geographic factors played a more significant role than environmental factors in driving microbial community variation. The study also revealed differences in environmental adaptability among different microbial types. Bacteria exhibited strong adaptability to salinity, while protists demonstrated greater resilience to variations in dissolved oxygen, nitrate, and ammonium concentrations. These results suggested differences in environmental adaptation strategies among microorganisms at different trophic levels, with bacteria demonstrating a more pronounced environmental filtering effect.